Added benefits: Reduced depressive symptom levels among African-American female adolescents participating in an HIV prevention intervention - Brown, Jennifer L. (2013)
BACKGROUND: Adolescents experience elevated depressive symptoms which health promotion interventions may reduce. PURPOSE: This study investigated whether HIV prevention trial participation decreased depressive symptoms among African-American female adolescents. METHODS: Adolescents (N=701; M age = 17.6) first received a group-delivered HIV prevention intervention and then either 12 sexual health (intervention condition) or 12 general health (comparison condition) phone counseling contacts over 24 months. ACASI assessments were conducted at baseline, and at 6-, 12-, 18-, and 24-months post-baseline. Linear generalized estimating equations were used to detect percent relative change in depressive symptoms. RESULTS: Participants reported a 2.7% decrease in depressive symptoms (p = 0.001) at each assessment. Intervention participants endorsed an additional 3.6% decrease in depressive symptoms (p = 0.058). CONCLUSIONS: Trial participation was associated with reduced depressive symptomatology, particularly among those receiving personalized sexual health counseling. HIV prevention interventions may benefit from incorporating additional content to address adolescents’ mental health needs.